2016
DOI: 10.1159/000446161
|View full text |Cite
|
Sign up to set email alerts
|

Living Kidney Donors Who Develop Kidney Failure: Excerpts of Their Thoughts

Abstract: Background: Psychosocial data about living kidney donors have been collected for almost 5 decades now. To date, however, no study has provided any psychosocial follow-up of donors who developed a serious health problem such as end-stage renal disease (ESRD). Methods: Donors who developed ESRD were invited to participate in a qualitative interview if they met one or both of the inclusion criteria: (1) developed ESRD within 10 years of donating and/or (2) lacked health insurance at the time of donation. We conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Given follow‐up time of only several years, most donors in this cohort would not have yet had time to experience long‐term health consequences, which might change their assessment of whether the donation decision was a good one. On the other hand, other studies have revealed that donors rarely regret their decision to donate . Finally, the self‐assessment about changes in life as a consequence of being accepted or turned down for kidney donation was not a validated measure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given follow‐up time of only several years, most donors in this cohort would not have yet had time to experience long‐term health consequences, which might change their assessment of whether the donation decision was a good one. On the other hand, other studies have revealed that donors rarely regret their decision to donate . Finally, the self‐assessment about changes in life as a consequence of being accepted or turned down for kidney donation was not a validated measure.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, other studies have revealed that donors rarely regret their decision to donate. 48,49 Finally, the self-assessment about changes in life as a consequence of being accepted or turned down for kidney donation was not a validated measure.…”
Section: Life Worse (N = 13)mentioning
confidence: 99%
“…The donor's perception on donation consequences for themselves, the recipient and their relationship before and after transplantation has mostly been described in retrospective or qualitative studies [12][13][14][15][16]. Furthermore, the presence or absence of regret about the donation decision has mostly been assessed using a single ad hoc question which has indicated that a small subgroup of donors experiences regret [13,[17][18][19]. Previous research assessing decisional regret about healthcare decisions in other patient populations showed that more regret was related to poorer HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…The full methodology is presented elsewhere. 7 In brief, we conducted semistructured interviews with living donors who developed ESRD after donating to a first-degree relative other than parent-to-child. Interviews were conducted by medical students and overseen by a physician-philosopher (L.F.R.)…”
Section: Methodsmentioning
confidence: 99%
“…Coding disagreements were reconciled with high intercoder reliability (>90%). 8 Participants are identified by gender (F, female; M, male), by the group from which they were recruited (T ¼ under 10 years; I ¼ uninsured), and by a unique number based on our recruiting method (for full details, see the study by Halverson et al 7 ).…”
Section: Collecting and Analyzing Informationmentioning
confidence: 99%